2004
DOI: 10.1200/jco.2004.03.086
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants and Cancer Therapy: A Systematic Review

Abstract: These inconsistencies preclude a definitive conclusion as to the effect of chemotherapy on antioxidant status in patients undergoing anticancer therapy. However, our review suggests that total antioxidant status (measured by total radical antioxidant parameter) declines during cancer treatment. Adequately powered trials or observational studies among patients with a specific cancer diagnosis receiving a specific treatment regimen are needed to address patients' and physicians' concerns regarding these associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
2
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 228 publications
(144 citation statements)
references
References 57 publications
3
126
2
10
Order By: Relevance
“…No evidence has been found that antioxidant vitamin supplements reduce the toxicity associated with chemotherapy [64]. Some authors even advise against the use of antioxidant supplements during chemotherapy or radiotherapy [65].…”
Section: Other Dietary Macro-and Micronutrientsmentioning
confidence: 99%
“…No evidence has been found that antioxidant vitamin supplements reduce the toxicity associated with chemotherapy [64]. Some authors even advise against the use of antioxidant supplements during chemotherapy or radiotherapy [65].…”
Section: Other Dietary Macro-and Micronutrientsmentioning
confidence: 99%
“…1,2 Currently, the use of antioxidant supplements during radiation therapy is a controversial issue, since it is feared that they could interfere with treatment. 3,4 We conducted a double-blind, placebo-controlled, randomized trial among head and neck cancer patients treated by radiation therapy to assess the effects of a supplementation combining alpha tocopherol and beta carotene on outcomes of head and neck cancer patients.…”
mentioning
confidence: 99%
“…[24][25][26] The idea that antioxidants might protect cancer cells from effects of cytotoxic chemotherapy or radiation is not yet clearly supported by evidence. 11,27 However, the ability to study supplement use rigorously in both cancer prevention and treatment has been limited by the lack of standardization of supplement formulations and dosing. [28][29][30] Despite the unclear benefits of supplements, use tends to increase after a cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Supplement use is common in patients with cancer (26% to 87%) and in patients with liver disease (27% to 43%), [7][8][9] despite the lack of clear evidence regarding efficacy or safety. 7,10,11 Our goal was to measure the prevalence of dietary supplement use in a prospective study of subjects with HCC and to determine demographic and clinical characteristics associated with supplement use. In this study, we also examined whether use of these agents was associated with overall survival.…”
Section: Introductionmentioning
confidence: 99%